Guidelines for preparing a design and monitoring framework soverign operations and technical assistance. (Metro Manila, Philippines Asian Development Bank, 2020)
These guidelines describe how a project level design and monitoring framework should be developed and used throughout the project cycle for Asian Development Bank (ADB) sovereign operations and technical assistance projects. The design and monitoring framework is a key tool for project design, implementation, and evaluation, and provides the basis for ADBs project performance management system. The guidelines are intended to help staff of ADB, government officers, consultants, project sponsors and borrowers, and other stakeholders prepare high quality design and monitoring frameworks. They serve as an effective tool to ensure that ADB-financed projects contribute to achieving a prosperous, inclusive, resilient, and sustainable Asia and Pacific region as envisaged in ADBs Strategy 2030. For guidance specific to private sector operations, consult ADBs Guidelines for Preparing and Using a Design and Monitoring Framework: Private Sector Operations.
Keywords: Economic assistance -- Developing countries -- Management; Economic development projects -- Developing countries -- Management; Economic assistance -- Management; Electronic books